Social Anxiety, Stress Type, and Conformity among Adolescents - Zhang, Peng; Deng, Yanhe; Yu, Xue; Zhao, Xin; Liu, Xiangping (Frontiers in Psychology, 2016)
Social anxiety and stress type can influence strong conformity among adolescents; however, the interaction between them is not clear. In this study, 152 adolescents were recruited and assigned one of two conditions: an interaction and a judgment condition. In the interaction condition, adolescents with high social anxiety were less likely to conform when completing a modified Asch task, compared to adolescents who had low social anxiety. In the judgment condition, adolescents with high social anxiety were more likely to conform to the opinions from the unanimous majority. The results suggest that adolescents with high social anxiety may show different styles of strong conformity with the change of stress type. We believe that socially anxious adolescents avoid potential social situations with weaker conformity, while avoiding negative evaluations from others with stronger conformity. These findings contribute to a better understanding of the social dysfunctions among adolescents with high social anxiety and provide a new direction for clinical interventions.